Smart biodegradable hydrogels incorporating a photoactive Ir(III) complex for NIR-triggered oral cancer treatment - Fang Yang; Ning Luo; Lizhen Ren; Wei Ding; Xuesong Wu (Cancer Nanotechnology)
Abstract Background Oral squamous cell carcinoma (OSCC) is the most common cancer in the head and neck region, accounting for nearly 90% of oral cavity tumors. OSCC cells often overexpress epidermal growth factor receptor (EGFR), which is linked to tumor formation, progression, and differentiation. Surgery and chemotherapy are the main treatments for OSCC, but they are ineffective compared to other oral cancers. Method To overcome these restrictions, anticancer-active Ir(III) complex-based photosensitizers are incorporated into a PANI-PEG-CS hydrogel and delivered to tumorous tissue, where they are activated by near-infrared (NIR) light to combat cancer. Results Hydrogels incorporating Ir(III) complex could be ingested by OSCC cells under NIR irradiation and have shown strong selectivity toward mitochondria. Further investigations confirmed that Ir increased ROS formation, decreased mitochondrial membrane potential, and depleted ATP levels, all of which led to OSCC cell apoptosis at 62.5 µg/ml. Western blot analysis showed that Ir(III)@PANI-PEG-CS hydrogel induces apoptosis in CAL-27 cells by activating the mitochondria-dependent apoptotic pathway and the PI3K/AKT pathway. Conclusion Nanocomposites selectively accumulate in malignant cells and effectively eliminate them using NIR irradiation. We conclude that complex Ir(III)@PANI-PEG-CS hydrogel may be a promising candidate for new anticancer therapies. Graphical Abstract